A relação da hospitalidade por meio dos intermediadores da mobilidade corporativa e seus stakeholders: um estudo de casos múltiplos em travel management company, online travel agency e consolidadora - CHUECO, Beatriz Godini (2017)
Hospitality is a sign of humanity; it is possible to observe that it is a limit of geography and civilized and wild boundary. The focus on product and service of the hotel and restaurant sectors complement as definitions of hospitality through the administration of hospitality that is dedicated to food, beverage and service as a service management. When we approach the stakeholder, the first concept is defined by a group of people who are part of a company or a group or an individual that can be affected or affect by the environment that belongs. The growing of the corporate mobility in recent times, it was facilitated by Globalization, which facilitates a fast exchange of communication, allows new technological achievements and fosters exchanges of knowledge, corporate mobility includes the coming and going with a commercial interest in business travel. The services are part of the corporate mobility and are related to hospitality and receive the host for the guest, even if it is by the optics of a company and client. Based on the current concepts and the interest of the researcher in the area, we reached a research problem: how intermediary services , here considered, distribution channels of corporate mobility create strategies through its stakeholders and hospitality management, after identified the problematic, it was possible to think about the general objective of the research in search of a relationship between the hospitality and the stakeholders of the distribution channels, the corporate mobility through its services. Through its specific objectives, it sought to identify key stakeholders of corporate mobility intermediaries and contributory hospitality management for clients as service clients. To meet the research proposal with tested three proposals: P1) The stakeholders of the corporate mobility intermediaries act under a hospitality administration to deliver their services; P2) An organization has taken on the role of host with its employees to convey the benefits of its management to its customers; P3) The hospitality relationship, through the interveners of the corporate mobility intermediaries, is present in the process. As a methodology, an empirical, qualitative and exploratory research was carried out, composed by the theoretical reference, a multiple case study, according to the teachings of Yin (2005) and semi-structured interview application, whose data were categorized and analyzed by the technique Of Content Analysis proposed by Bardin (1977). The results obtained consider that hospitality is present in the intermediaries of the corporate mobility and its stakeholders, in both scenarios is possible to identify it.